Research Framework for the Construction of Developmental Support and Education System in Vocational Colleges - A Case Study of Shang Rao Vocational College - Dong, Rao (Pacific International Journal, 2024)
This study investigates the construction of developmental support and education systems in vocational colleges, with a specific focus on the "riser" Project at Shang Rao Vocational College, Jiangxi province, China. Recognizing the evolving needs of economically disadvantaged students, the study explores the efficacy of holistic developmental support initiatives beyond traditional financial aid. Through a mixed-methods approach incorporating theoretical frameworks, empirical data analysis, and stakeholder insights, the study evaluates the effectiveness of existing support systems and identifies areas for improvement. Key findings highlight the significance of integrated support services in fostering students' academic, personal, and professional growth. The "riser" Project emerges as a notable exemplar of comprehensive developmental support within vocational education settings, though opportunities for refinement are evident. Practical recommendations are offered to optimize support services and enhance student experiences, contributing to the advancement of vocational education in the post-poverty era.